Prenatal diagnosis of congenital femoral deficiency and fibular hemimelia1. (15th May 2014) - Radler, Christof; Myers, Abigail K.; Hunter, Renee J.; Arrabal, Pedro P.; Herzenberg, John E.
ABSTRACT Objectives Routine ultrasonography can detect congenital femoral deficiency (CFD) and fibular hemimelia (FH), but prenatal detection rate and its relation to deformity severity have never been reported. Whether mothers prefer prenatal diagnosis is also unknown. We aimed to determine whether mothers prefer prenatal diagnosis, to report detection rates for CFD and/or FH, and to correlate detection rates to severity of limb shortening. Methods Surveys were mailed to 171 mothers who gave birth to children with CFD/FH between 2000 and 2008. Bilateral femoral and tibial lengths were measured on postnatal radiographs. We calculated corresponding femoral/tibial lengths at gestational weeks 20 and 30. Results Sixty‐five surveys were returned, and 56 radiographs were reviewed. Most mothers (63%) preferred prenatal diagnosis as it enables prenatal counseling. Congenital limb shortening was detected in 24 cases (37%) and was not detected in 41 cases (63%). Detection rate was 52% (12 of 23) in CFD cases, 23% (three of 13) in FH cases, and 30% (six of 20) in combined cases. CFD cases with severe shortening had a higher detection rate. Conclusions Ultrasonographers should measure both femoral and tibial lengths. Unilateral shortening should result in pediatric orthopedic consultation to estimate limb‐length discrepancy at maturity and discuss treatment. © 2014 John Wiley & Sons, Ltd.